Answer:
Let's assume that Mia's present age is x.
According to the problem, Rosie is 6 years older than Mia, so Rosie's present age is x + 6.
In 4 years, Mia's age will be x + 4, and Rosie's age will be (x + 6) + 4 = x + 10.
The problem also states that Rosie's age in 4 years will be three times Mia's present age, so we can write the equation:
x + 10 = 3x
Simplifying this equation, we can subtract x from both sides to get:
10 = 2x
Dividing both sides by 2, we get:
x = 5
Therefore, Mia is currently 5 years old. To check, we can verify that in 4 years, Rosie will be three times Mia's age:
Rosie's age in 4 years = (5 + 6) + 4 = 15
Mia's age in 4 years = 5 + 4 = 9
Rosie's age in 4 years is indeed three times Mia's age, so our solution is correct.